The Effect of Marketing Partnership and Sales Promotion on the Purchase Intention of the Sei Sapi Mancuy Brand on Grabfood Super Apps in Lengkong, Cicendo, Cibeunying Kaler, Sukasari, and Cinambo Districts - Munir, Achmad Saepul; Eithan, Revan Gabe; Nurhandayani, Syifa (International Journal Labs, 2025)
The rapid growth of online food delivery services in Indonesia, particularly following the COVID-19 pandemic, has intensified competition among brands on super-app platforms such as GrabFood. In this dynamic digital marketplace, effective marketing strategies are essential for influencing consumer purchase decisions. This research aims to analyze the effect of marketing partnership and sales promotion on the purchase intention of the Sei Sapi Mancuy brand on the GrabFood super-app service in Bandung City. The background of this study is rooted in the rapid advancement of information and communication technology, which has driven the expansion of the online food delivery service industry, especially after the COVID-19 pandemic. This research employed a quantitative approach by distributing questionnaires to 100 respondents who had used GrabFood in five districts: Lengkong, Cicendo, Cibeunying Kaler, Sukasari, and Cinambo. Data were analyzed using multiple linear regression to assess the influence of the independent variables on purchase intention. The results indicate that marketing partnership and sales promotion jointly explain 71.7% of the variation in purchase intention, with partial contributions of 13.7% from marketing partnership and 58.0% from sales promotion. Hypothesis testing confirms that both variables have a significant effect, both partially and simultaneously, with a very strong correlation level (R = 0.847). The study concludes that while both variables significantly influence purchase intention, sales promotion exerts a more dominant impact. These findings offer managerial implications for strengthening collaborative marketing strategies and optimizing promotional programs to enhance consumer purchase intention on digital platforms.